FRAKSI SERAT SILASE KULIT PISANG KEPOK (Musa paradisiaca) MENGGUNAKAN PENAMBAHAN LEVEL DEDAK DAN LAMA FERMENTASI YANG BERBEDA - Sari Handayani; Eniza Saleh; Anwar Efendi Harahap (Jurnal Peternakan, 2018)
Banana peels not much optimally used as a substitute for grass. In 2014 the production of banana peels waste Riau province reaches 7.586 ton. More than a third of the banana that has not been in the strip is banana peels. The purpose of this study to determine the effect with different rice bran level and fermentation time of the fiber fraction silage that includes the content of neutral detergent fiber (NDF), acid detergent fiber (ADF), acid detergent lignin (ADL), hemicellulose, and cellulose. This research was conducted at the Laboratory of Nutrition Science and Chemistry, Faculty of Agriculture and Animal Science State Islamic University of Sultan Syarif Kasim Riau Pekanbaru. The research was conducted in April until September 2016. This study were an experimental study using a completely randomized design pattern Factorial consisting of rice bran level (0; 5; and 10%) and fermentation time (0; 14; and 28 days), each treatment was repeated 2 times. There were no significant differences (P>0,05) in NDF, ADF, ADL, hemicelluloses, and cellulose. It can be concluded that there is not interaction between rice bran level and fermentation time toward fiber fraction of banana peels silage.